“Sistema Automatizado de Gestión de Información para la Clínica Veterinaria de la Universidad Técnica de Cotopaxi” - Martínez Freire, Maira Natalia (2020)
The UTC veterinary clinic manually performs the processes related to the medical history of patients, care and other information generated in the different areas of the clinic, which implies that the tasks inherent to the clinical care activity are they become limiting and do not allow their effective administration. For this reason the objective of the study en Develop a cloud-oriented computing system through the use of the architecture view controller model, for information management in the veterinary clinic of the Faculty of Agricultural Sciences and Natural Resources of the Technical University of Cotopaxi, with the implementation of the computer system will save all the data of the clients and their pets with their medical records within a database and can be performed more precise searches by entering the names of the patients or the main data of the owner and thus simplify the search and find the medical file more quickly, in addition the client will be able to access the necessary information of their pets and will be able to view the necessary reports such as the vaccination and deworming certificate with this it is about provide a tailored solution that meets the needs that arise in the clinic veterinary and that once the application is started, each problem generated is solved in the clinic. The agile methodology has been used for the software development process SCRUM in order to maintain an adequate order in the different activities required for the implementation of the automated information management system for the veterinary clinic, in this sense the following artifacts have been used: Product backlog and Sprint backlog. The architecture chosen for the automated information management system It is an avant-garde development tool since it uses the controller view model that allows the development of applications in a web environment in an orderly manner; in that sense, it has a server connected to the internet where the apache web server is installed, the MySQL database and the PHP programming language that allow the accessibility of those interested in the SI such as veterinarians, administrator, laboratory worker, interns and above all to customers who enter the system through any web browser they have installed on their computers in order that the activities carried out within it are agile and efficient for the benefit of the user.